2018
DOI: 10.1002/etc.4236
|View full text |Cite
|
Sign up to set email alerts
|

An amphibian with a contracting range is not more vulnerable to pesticides in outdoor experimental communities than common species

Abstract: In areas with heavy pesticide use, it is easy to attribute population declines to environmental contamination. The Blanchard's cricket frogs (Acris blanchardi) is an amphibian experiencing declines and range contractions across its distribution in the Midwest Corn Belt (USA). Experimental studies suggest that cricket frogs are sensitive to pesticides, but there are few studies examining this species' susceptibility to contaminants in realistic environments or comparing relative impacts with other anuran specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…A reduction in survival for northern cricket frogs ( Acris crepitans ) was found with exposure to extreme concentrations of imidacloprid (i.e., 9000 µg/L; Ade et al ). In addition, Blanchard's cricket frogs ( Acris blanchardi ) chronically exposed to 1000 µg/L of imidacloprid had larger mass at metamorphosis compared to controls (Boone ). However, no adverse effects of neonicotinoid exposure were detected in green frogs ( Lithobates clamitans ) exposed to imidacloprid up to 9000 µg/L (Ade et al ).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in survival for northern cricket frogs ( Acris crepitans ) was found with exposure to extreme concentrations of imidacloprid (i.e., 9000 µg/L; Ade et al ). In addition, Blanchard's cricket frogs ( Acris blanchardi ) chronically exposed to 1000 µg/L of imidacloprid had larger mass at metamorphosis compared to controls (Boone ). However, no adverse effects of neonicotinoid exposure were detected in green frogs ( Lithobates clamitans ) exposed to imidacloprid up to 9000 µg/L (Ade et al ).…”
Section: Introductionmentioning
confidence: 99%
“…R. clamitans tadpoles exposed to environmentally relevant carbaryl concentrations did not have altered metamorphosis according to morphological metrics: tadpole development and time to metamorphosis (91, 175). However, both short- and long-term alterations in gene expression were observed in brain and tail tissues of tadpoles acutely exposed to carbaryl at 8 and 16 weeks post-hatching (Table 3) (91).…”
Section: Industrial and Agricultural Chemicalsmentioning
confidence: 89%
“…With respect to anuran metamorphosis, delays in completion have been reported for Xenopus laevis exposed to 20 and 100 mg/L of TIA and clothianidin (Jenkins et al, 2021), Lithobates pipiens tadpoles exposed to 8.5 mg/L and 250 ng/L of IMI (Moe et al, 2007), and Lithobates sylvaticus tadpoles exposed to 1 µg/L, 10 µg/L and 100 µg/L of IMI, although, in this case, the same concentrations of TIA had no effect on development time (Robinson et al, 2017). A lack of effect on development time was also reported for tadpoles of Acris blanchardi, Lithobates clamitans and Hyla chrysosceli exposed to 1 mg/L of IMI (Boone, 2018), Rana pipiens exposed to 2.5 and 250 ug/L of clothianidin and TIA (Robinson et al, 2019), and to 0,23, 1, 10 and 100 µg/L of clothianidin (Robinson et al, 2021). Finally, larvae of the Northwestern salamander (Ambystoma gracile) presented, in contrast, accelerated development, when exposed to 100 μg/L of IMI (Danis and Marlatt, 2021).…”
Section: Introductionmentioning
confidence: 64%
“…Although a number of studies had previously examined the impact of the neonicotinoids on amphibian tadpoles, this is the rst time that the progression through the different stages is closely monitored and an impact on the thyroid system can be pinpointed. Most previous studies focused on the time to metamorphosis and a variety of results including retardement, acceleration or lack of effect have been reported (Moe et al, 2007;Robinson et al, 2017;2019;Boone et al, 2018;Jenkins et al, 2021;Danis and Marlatt, 2021). Here, although a slight acceleration of T50-MET is observed at the largest exposure concentrations, it is shown that the main effects of TIA is a systematic decrease in the metamorphic success and smaller size at metamorphosis; two effects that can clearly impair amphibian performance and survival in the wild.…”
Section: Discussionmentioning
confidence: 99%